2017
DOI: 10.1111/tid.12662
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus interaction with nafcillin resulting in significant decreases in tacrolimus concentrations: A case report

Abstract: Tacrolimus (TAC) is subject to many drug interactions as a result of its metabolism primarily via CYP450 isoenzyme 3A4. Numerous case reports of TAC and CYP3A4 inducers and inhibitors have been described including antimicrobials, calcium channel antagonists, and antiepileptic drugs. We present the case of a 13-year-old patient with cystic fibrosis and a history of liver transplantation, where subtherapeutic TAC concentrations were suspected to be a result of concomitant TAC and nafcillin (NAF) therapy. The obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…To investigate the mechanism of antagonism, we looked to other known drug interactions involving nafcillin. In particular, nafcillin antagonizes warfarin and other drugs in vivo by inducing cytochrome P450 enzymes through an unknown mechanism, which increases warfarin metabolism (King et al, 2018;Wungwattana and Savic, 2017). FLZ inhibits a fungal cytochrome P450 enzyme, 14a-demethylase, which halts ergosterol biosynthesis and fungal growth (Figure 5N; Odds et al, 2003).…”
Section: Exposure To Beta-lactam Antibiotics Increases Ergosterol Levels and Antagonizes Fluconazole Activitymentioning
confidence: 99%
“…To investigate the mechanism of antagonism, we looked to other known drug interactions involving nafcillin. In particular, nafcillin antagonizes warfarin and other drugs in vivo by inducing cytochrome P450 enzymes through an unknown mechanism, which increases warfarin metabolism (King et al, 2018;Wungwattana and Savic, 2017). FLZ inhibits a fungal cytochrome P450 enzyme, 14a-demethylase, which halts ergosterol biosynthesis and fungal growth (Figure 5N; Odds et al, 2003).…”
Section: Exposure To Beta-lactam Antibiotics Increases Ergosterol Levels and Antagonizes Fluconazole Activitymentioning
confidence: 99%
“…Several studies showed that CYP3A4, CYP3A5 and ABCB1 gene polymorphisms play a crucial role in tacrolimus metabolism and excretion [8,9]. In particular, the pharmacokinetics of tacrolimus is mainly influenced by drug interaction, which is subject to numerous inhibitors or inducers of the CYP3A4/5 enzyme.…”
Section: Introductionmentioning
confidence: 99%